Comparative study of Cu films prepared by DC, high power pulsed and burst magnetron sputtering; Journal of Electronic Materials; Vol. 45, iss. 8 - Soloviev (Solovyev) A. A. Andrey Aleksandrovich; Oskirko V. O. Vladimir Olegovich; Semenov V. A. Vyacheslav Arkadjevich; Oskomov K. V. Konstantin Vladimirovich; Rabotkin S. V. Sergey Viktorovich (2016, 2016)
Title screen